High-transmittance ceramic material and preparation method thereof

Through specific raw materials and process steps, the problems of pore grain boundaries and microcracks in translucent piezoelectric ceramics are solved, the transmittance and mechanical strength are improved, and the piezoelectric performance is enhanced.

CN120647365AActive Publication Date: 2025-09-16ENPING XINJINCHENG CERAMICS CO LTD

Patent Information

Application Number
CN202510966822.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-09-16
Estimated Expiration
2045-07-14

AI Technical Summary

Technical Problem

During the sintering process, light-transmitting piezoelectric ceramics are prone to the formation of pores, grain boundaries and microcracks, which lead to light scattering, reduce light transmittance and affect mechanical properties.

Method used

Sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide and zirconium dioxide are used as raw materials. Through the steps of one-time ball milling, drying, pre-firing, ball milling, pressing, sintering, polishing and heat treatment, a composite slurry of silica-titania sol and silver paste is sprayed to form a dense conductive layer to fill the pores and cracks.

Benefits of technology

It significantly improves the optical transmittance, piezoelectric properties and mechanical strength of ceramic materials, reduces light scattering, and enhances the density and mechanical properties of ceramics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of piezoelectric light-transmitting functional ceramics, and discloses a high-light-transmitting ceramic material and a preparation method thereof.The preparation method comprises the following preparation steps that sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium oxide and zirconium dioxide powder raw materials are taken, and after primary ball milling and drying are conducted on the powder raw materials, mixed powder is obtained; carrying out pre-sintering and secondary ball milling on the mixed powder, carrying out compression molding to form a tablet, and sintering and polishing the tablet to obtain a ceramic matrix; and spraying the composite slurry to the surface of a ceramic matrix, carrying out heat treatment, and cooling to room temperature to obtain the high-transmittance ceramic material. The antimony trioxide, the samarium oxide and the zirconium dioxide are co-doped, an antimony-samarium-zirconium liquid phase is generated in the ceramic material, pores of the ceramic material are filled and eliminated, and the prepared ceramic material has excellent optical transmittance, piezoelectric property and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric light-transmitting functional ceramics, in particular to a high-light-transmitting ceramic material and a preparation method thereof. Background Art

[0002] Transparent ceramic materials are a general term for ceramic materials that can transmit visible light. They have piezoelectricity and transparency and can be used to manufacture high-voltage electrodes, transparent sensors, transparent electronic devices, etc. Transparent piezoelectric ceramics have excellent physical properties of piezoelectricity, ferroelectricity, and electromagnetic properties, and have the characteristics of high strength, high transparency, high thermal stability, and high corrosion resistance. Currently, ion doping is a relatively effective method to optimize its performance and realize new functions. It can realize the "force-acoustic-optical-electrical" multi-physical field coupling effect and is widely used in solar cells, LED lighting, medical equipment, safety glass, aerospace and other fields.

[0003] Transparent piezoelectric ceramics are prepared through powder sintering technology. During the sintering process, defects such as pore grain boundaries and microcracks are prone to appear in the transparent ceramic material. These defects cause light scattering and reduce the transmittance. The cracks produced lead to poor mechanical properties of the transparent piezoelectric ceramics, affecting the service life of the transparent piezoelectric ceramics. Summary of the Invention

[0004] The present invention provides a high-light-transmittance ceramic material and a preparation method thereof, which solves the problem that light-transmitting piezoelectric ceramics are prone to pore grain boundaries and microcracks.

[0005] The technical solution of the present invention:

[0006] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0007] S1. Take sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide, zirconium dioxide powder raw materials, the powder raw materials were once ball milled and dried to obtain a mixed powder;

[0008] S2. The mixed powder is pre-sintered, ball-milled twice, and then pressed to form a tablet, which is sintered and polished to obtain a ceramic matrix;

[0009] S3. Spray the composite slurry onto the surface of the ceramic substrate, heat treat it, and cool it to room temperature to obtain a highly transparent ceramic material.

[0010] Furthermore, in step S1, the mass ratio of sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide, and zirconium dioxide is (2.5-2.6):(3.2-3.4):(13.2-13.5):(0.6-0.8):(0.2-0.3):(0.1-0.2).

[0011] Furthermore, in step S1, the drying temperature is 80-100° C., and the drying time is 20-24 hours.

[0012] Furthermore, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 8-10 mm are used as grinding balls, the ball-to-material ratio is (1.4-1.6):1, and the ball milling speed is 220-230 r / min;

[0013] Furthermore, in step S1 and step S2, the first ball milling time is 20-24 hours; the second ball milling time is 10-12 hours.

[0014] Furthermore, in step S2, the pre-firing temperature is 800-900°C, the pre-firing time is 4-6 hours, the pre-firing medium is nitrogen, and the nitrogen flow rate is 5-10 L / min.

[0015] Furthermore, in step S2, the pressing pressure is 150-250 MPa.

[0016] Furthermore, in step S2, the sintering temperature is 1150-1200°C, and the sintering time is 5-7 hours.

[0017] Furthermore, in step S2, sandpaper and corundum are used for polishing until the thickness of the ceramic substrate is 0.5-0.6 mm.

[0018] Furthermore, in step S3, the heat treatment temperature is 800-900° C., and the heat treatment time is 25-35 minutes.

[0019] Furthermore, in step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:(5-10).

[0020] Furthermore, in step S3, the spraying amount of the composite slurry is 50-60 g / m 2 , the spraying pressure is 0.3-0.5MPa.

[0021] Furthermore, the silica-titania sol is prepared by mixing silica sol and titania sol in a mass ratio of 1:(0.8-1.2).

[0022] Furthermore, the silica-titania sol is specifically prepared by the following steps:

[0023] A1. Add ethyl orthosilicate to ethanol and deionized water, stir at 55-65 ° C for 1-2 hours, cool to room temperature, add hydrochloric acid to adjust the pH to 2-3, and continue stirring to obtain a silica sol;

[0024] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 40-50 ° C for 1-2h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 2-3. After continued stirring, a titanium dioxide sol was obtained;

[0025] A3. Silica sol and titania sol were mixed in a mass ratio of 1:(0.8-1.2), stirred at 55-65°C for 1-3h to form a transparent homogeneous sol, cooled to room temperature, and continued stirring to obtain silica-titania sol.

[0026] Furthermore, during the above reaction process, ethyl orthosilicate and tetrabutyl titanate are hydrolyzed to form silica sol and titania sol respectively, and the silica sol and titania sol are combined through chemical bonds to form a silica-titania sol with a cross-linked network structure.

[0027] Furthermore, in step A1, the mass ratio of ethyl orthosilicate, ethanol and deionized water is (18-22):(35-45):(8-12).

[0028] Furthermore, in step A2, the mass ratio of tetrabutyl titanate, ethanol and deionized water is (13-17):(30-40):(8-12).

[0029] A high-light-transmittance ceramic material is prepared by the above-mentioned method for preparing the high-light-transmittance ceramic material.

[0030] The present invention has the following beneficial effects:

[0031] (1) In the technical solution of the present invention, sodium carbonate, potassium carbonate and niobium pentoxide are used as the matrix of the light-transmitting ceramic material, and antimony trioxide, samarium trioxide and zirconium dioxide are used as the solid solution phase, so that the ceramic material has excellent light-transmitting properties. In addition, antimony trioxide, samarium trioxide and zirconium dioxide effectively regulate the phase structure of the ceramic, so that the ceramic is in a pseudo-cubic phase structure in which tetragonal phase and cubic phase coexist, which significantly improves the optical transmittance, piezoelectric properties and mechanical strength of the ceramic material.

[0032] (2) In the technical solution of the present invention, the samarium ions in samarium trioxide can preferentially replace the sodium ions in the A position, forming samarium sodium defects, compensating for the oxygen vacancy charge, regulating the phase structure and optical properties, reducing visible light absorption, and making the ceramic material have a higher transmittance; the antimony ions in antimony trioxide can replace niobium, induce the formation of phase boundaries, and inhibit oxygen vacancies, avoiding the formation of oxygen vacancies and causing yellowing; the zirconium ions in zirconium dioxide can also replace niobium, which has the effect of refining the grains and enhancing the mechanical strength of the ceramic material. In addition, zirconium dioxide can form a high melting point phase, hindering grain boundary migration, improving the density of the ceramic material, reducing the occurrence of pores, and improving the transmittance;

[0033] In addition, antimony trioxide, samarium trioxide and zirconium dioxide are co-doped to generate an antimony-samarium-zirconium liquid phase in the ceramic material, filling and eliminating the pores of the ceramic material to avoid the presence of pores that cause light scattering and reduce transmittance; and antimony trioxide, samarium trioxide and zirconium dioxide are coated on the surface of the sodium carbonate, potassium carbonate and niobium pentoxide base materials to inhibit the volatilization of potassium, sodium and niobium in the base materials, thereby improving the density of the ceramic material and making the prepared ceramic material have excellent optical transmittance, piezoelectric properties and mechanical strength.

[0034] (3) In the technical solution of the present invention, a mixture of silica-titania sol and silver paste is sprayed on the surface of a ceramic substrate and heat-treated at 850°C to form a transparent piezoelectric ceramic. The silver paste is sprayed on the surface of the ceramic substrate to form a dense conductive layer on the surface of the ceramic substrate, thereby improving the piezoelectric performance. The silver paste reacts with the ceramic substrate to eliminate residual pores inside the ceramic and improve the light transmittance.

[0035] The composite slurry is applied to the surface of a ceramic substrate. On the one hand, the silica-titania sol and silver paste form a gradient refractive index layer consisting of a silica-titania sol layer and a silver layer on the ceramic substrate surface, reducing interface reflection and scattering losses and improving light transmittance. On the other hand, the composite slurry can penetrate cracks and pores on the surface of the ceramic substrate. After heat treatment at 850°C, the silica-titania sol reacts with the ceramic substrate to form a silicate / titanate interface layer, which improves the peel strength of the silver layer and prevents it from falling off, which would otherwise reduce the light transmittance and piezoelectric properties of the translucent ceramic.

[0036] The silicon dioxide and titanium dioxide that penetrate into the ceramic matrix can form a silicate glass phase with the ceramic matrix, fill the grain boundary pores, and thus improve the transmittance of the ceramic material, and improve the density and mechanical properties. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0038] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.

[0039] The purity of sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide and zirconium dioxide is 99.99%.

[0040] The silver paste model is S-200G, which was purchased from Shenzhen Qiandai Electronic Materials Co., Ltd.

[0041] Example 1

[0042] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0043] S1. Take 2.5g of sodium carbonate, 3.2g of potassium carbonate, 13.2g of niobium pentoxide, 0.6g of antimony trioxide, 0.2g of samarium trioxide, and 0.1g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 20h and dried at 80 ° C for 20h to obtain a mixed powder;

[0044] S2. The mixed powder was pre-calcined at 800 ° C for 4 h, the pre-calcination medium was nitrogen, and the nitrogen flow rate was 5 L / min; then the secondary ball milling was performed for 10 h, the pressing pressure was controlled to 150 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1150 ° C for 5 h and polished to obtain a ceramic substrate;

[0045] S3. Control the composite slurry spraying amount to 50g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.3 MPa, and after heat treatment at 800°C for 25 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0046] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.4:1, and the ball milling speed is 220 r / min;

[0047] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0048] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:5;

[0049] The silica-titania sol is specifically prepared by the following steps:

[0050] A1. Add ethyl orthosilicate to ethanol and deionized water, stir at 55°C for 1 hour, cool to room temperature, add hydrochloric acid to adjust the pH to 2, and continue stirring for 24 hours to obtain a silica sol; the mass ratio of ethyl orthosilicate, ethanol, and deionized water is 18:35:8;

[0051] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 40 ° C for 1 hour, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 2. Stirring was continued for 24 hours to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 13:30:8;

[0052] A3. Silica sol and titania sol were mixed in a mass ratio of 1:0.8, stirred at 55°C for 1 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0053] Example 2

[0054] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0055] S1. Take 2.55g of sodium carbonate, 3.25g of potassium carbonate, 13.35g of niobium pentoxide, 0.72g of antimony trioxide, 0.25g of samarium trioxide, and 0.15g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 22h and dried at 90 ° C for 22h to obtain a mixed powder;

[0056] S2. The mixed powder was pre-calcined at 850 ° C for 5 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 8 L / min, and then the secondary ball milling was carried out for 11 h. The pressing pressure was controlled to 200 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1170 ° C for 6 h and polished to obtain a ceramic substrate.

[0057] S3. Control the composite slurry spraying amount to 55g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.4 MPa, and after heat treatment at 850°C for 30 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0058] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.5:1, and the ball milling speed is 225 r / min;

[0059] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0060] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:8;

[0061] The silica-titania sol is specifically prepared by the following steps:

[0062] A1. Add ethyl orthosilicate to ethanol and deionized water, stir at 60°C for 1.5 hours, cool to room temperature, adjust the pH to 2.5 with hydrochloric acid, and continue stirring for 24 hours to obtain a silica sol; the mass ratio of ethyl orthosilicate, ethanol, and deionized water is 20:40:10;

[0063] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 45 ° C for 1.5 h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 2.5. Stirring was continued for 24 h to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 15:35:10;

[0064] A3. Silica sol and titania sol were mixed in a 1:1 mass ratio, stirred at 60°C for 2 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0065] Example 3

[0066] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0067] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 0.8g of antimony trioxide, 0.3g of samarium trioxide, and 0.2g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0068] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0069] S3. Control the composite slurry spraying amount to 60g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0070] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0071] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0072] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:10;

[0073] The silica-titania sol is specifically prepared by the following steps:

[0074] A1. TEOS was added to ethanol and deionized water, stirred at 65°C for 2 h, cooled to room temperature, and adjusted to pH 3 by adding hydrochloric acid. Stirring was continued for 24 h to obtain a silica sol; the mass ratio of TEOS, ethanol, and deionized water was 22:45:12.

[0075] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50 ° C for 2h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 3. Stirring was continued for 24h to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12;

[0076] A3. Silica sol and titania sol were mixed in a mass ratio of 1:1.2, stirred at 65°C for 3 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0077] Comparative Example 1

[0078] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0079] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 1.1g of samarium trioxide, and 0.2g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0080] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0081] S3. Control the composite slurry spraying amount to 60g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0082] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0083] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0084] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:10;

[0085] The silica-titania sol is specifically prepared by the following steps:

[0086] A1. TEOS was added to ethanol and deionized water, stirred at 65°C for 2 h, cooled to room temperature, and adjusted to pH 3 by adding hydrochloric acid. Stirring was continued for 24 h to obtain a silica sol; the mass ratio of TEOS, ethanol, and deionized water was 22:45:12.

[0087] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50 ° C for 2h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 3. Stirring was continued for 24h to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12;

[0088] A3. Silica sol and titania sol were mixed in a mass ratio of 1:1.2, stirred at 65°C for 3 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0089] Comparative Example 2

[0090] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0091] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 0.8g of antimony trioxide, and 0.5g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0092] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0093] S3. Control the composite slurry spraying amount to 60g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0094] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0095] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0096] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:10;

[0097] The silica-titania sol is specifically prepared by the following steps:

[0098] A1. TEOS was added to ethanol and deionized water, stirred at 65°C for 2 h, cooled to room temperature, and adjusted to pH 3 by adding hydrochloric acid. Stirring was continued for 24 h to obtain a silica sol; the mass ratio of TEOS, ethanol, and deionized water was 22:45:12.

[0099] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50 ° C for 2h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 3. Stirring was continued for 24h to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12;

[0100] A3. Silica sol and titania sol were mixed in a mass ratio of 1:1.2, stirred at 65°C for 3 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0101] Comparative Example 3

[0102] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0103] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 1g of antimony trioxide, and 0.3g of samarium trioxide powder raw materials. The powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0104] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0105] S3. Control the composite slurry spraying amount to 60g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0106] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0107] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0108] In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:10;

[0109] The silica-titania sol is specifically prepared by the following steps:

[0110] A1. TEOS was added to ethanol and deionized water, stirred at 65°C for 2 h, cooled to room temperature, and adjusted to pH 3 by adding hydrochloric acid. Stirring was continued for 24 h to obtain a silica sol; the mass ratio of TEOS, ethanol, and deionized water was 22:45:12.

[0111] A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50 ° C for 2h, cooled to room temperature, and hydrochloric acid was added to adjust the pH to 3. Stirring was continued for 24h to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12;

[0112] A3. Silica sol and titania sol were mixed in a mass ratio of 1:1.2, stirred at 65°C for 3 h to form a transparent homogeneous sol, cooled to room temperature, and stirred for 24 h to obtain silica-titania sol.

[0113] Comparative Example 4

[0114] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0115] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 0.8g of antimony trioxide, 0.3g of samarium trioxide, and 0.2g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0116] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0117] S3. Control the composite slurry spraying amount to 60g / m 2The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0118] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0119] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0120] In step S3, the composite slurry is prepared by mixing silica sol and silver paste in a mass ratio of 1:10;

[0121] Silica sol is specifically prepared by the following steps:

[0122] Tetraethyl orthosilicate was added to ethanol and deionized water, stirred at 65° C. for 2 h, cooled to room temperature, hydrochloric acid was added to adjust the pH to 3, and stirring was continued for 24 h to obtain a silica sol; the mass ratio of tetraethyl orthosilicate, ethanol, and deionized water was 22:45:12.

[0123] Comparative Example 5

[0124] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0125] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 0.8g of antimony trioxide, 0.3g of samarium trioxide, and 0.2g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0126] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0127] S3. Control the composite slurry spraying amount to 60g / m 2 The composite slurry was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0128] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0129] In step S2, 1500-grit sandpaper and 1500-grit corundum are used for polishing until the ceramic substrate has a thickness of 0.55 mm.

[0130] In step S3, the composite slurry is prepared by mixing titanium dioxide sol and silver paste in a mass ratio of 1:10;

[0131] Titanium dioxide sol is specifically prepared by the following steps:

[0132] Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, hydrochloric acid was added to adjust the pH to 3, and stirring was continued for 24 hours to obtain a titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12.

[0133] Comparative Example 6

[0134] A method for preparing a high-light-transmittance ceramic material comprises the following steps:

[0135] S1. Take 2.6g of sodium carbonate, 3.4g of potassium carbonate, 13.5g of niobium pentoxide, 0.8g of antimony trioxide, 0.3g of samarium trioxide, and 0.2g of zirconium dioxide powder raw materials, and the powder raw materials were ball-milled once for 24h and dried at 100 ° C for 24h to obtain a mixed powder;

[0136] S2. The mixed powder was pre-calcined at 900 ° C for 6 h, the pre-calcination medium was nitrogen, the nitrogen flow rate was 10 L / min, and then the secondary ball milling was carried out for 12 h. The pressing pressure was controlled to be 250 MPa, and the pressed tablets were formed by pressing. The tablets were placed at a sintering temperature of 1200 ° C for 7 h and polished to obtain a ceramic substrate.

[0137] S3. Control the silver paste spraying amount to 60g / m 2 The silver paste was sprayed onto the surface of the ceramic substrate at a spraying pressure of 0.5 MPa, and after heat treatment at 900°C for 35 minutes, it was cooled to room temperature to obtain a high-transmittance ceramic material.

[0138] Wherein, in step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, the zirconium balls with a diameter of 9 mm are used as grinding balls, the ball-to-material ratio is 1.6:1, and the ball milling speed is 230 r / min;

[0139] In step S2, 1500-mesh sandpaper and 1500-mesh corundum are used for polishing until the thickness of the ceramic substrate is 0.55 mm.

[0140] The performance of the high light transmittance ceramic materials prepared in Examples 1-3 and Comparative Examples 1-6 is now tested.

[0141] Vickers hardness test: The Vickers hardness of the high-transmittance ceramic material prepared above was tested using a hardness tester and an indentation method. The test conditions were: diamond indenter, force 10 kg, and test time 15 s.

[0142] Bending strength test: The flexural strength of the high light transmittance ceramic material prepared above was measured by a three-point bending method on an Instron-5569 universal testing machine.

[0143] Density test: The Archimedean drainage method was used to measure the density of the highly transparent ceramic material prepared above. The experimental instrument was a TG328A photoelectric analytical balance with an accuracy of one ten-thousandth of a gram.

[0144] Light transmittance test: A 77C-1 intelligent porcelain body light transmittance meter (purchased from Xiangtan Instrument Co., Ltd.) was used to test the light transmittance of the high-light transmittance ceramic material prepared above. The thickness of the high-light transmittance ceramic material was 1 mm, and the test light band was 800 nm.

[0145] Piezoelectric performance test: using quasi-static d 33 / d 31 The piezoelectric constant (25° C., pC / N) of the high-transmittance ceramic material prepared above was measured using a tester (model ZJ-3A, Institute of Acoustics, Chinese Academy of Sciences).

[0146] The test results are shown in Table 1 below.

[0147] Table 1 Performance test of high light transmittance ceramic materials prepared in Examples 1-3 and Comparative Examples 1-6

[0148] project Vickers hardness / MPa Bending strength / MPa <![CDATA[Density g / cm 3 > Transmittance / % Piezoelectric constant (25℃, pC / N) Example 1 25.6 460.2 4.85 82.3 453 Example 2 26.1 461.7 4.91 83.7 455 Example 3 24.8 459.5 4.78 81.6 450 Comparative Example 1 14.1 342.1 2.23 50.4 373 Comparative Example 2 15.6 341.6 2.35 45.8 381 Comparative Example 3 12.1 330.9 2.15 51.4 383 Comparative Example 4 18.9 400.1 3.11 63.5 412 Comparative Example 5 18.2 402.6 3.15 64.7 418 Comparative Example 6 16.2 385.9 2.95 55.6 405

[0149] It can be seen from the data in Table 1 that the high-transmittance ceramic materials prepared in Examples 1-3 have high transmittance, mechanical properties and piezoelectric properties.

[0150] In Comparative Example 1, the piezoelectric properties and transmittance of the high-transmittance ceramic materials prepared by replacing the mass of antimony trioxide with samarium trioxide, Comparative Example 2 replaces the mass of samarium trioxide with zirconium dioxide, and Comparative Example 3 replaces the mass of zirconium dioxide with antimony trioxide are reduced, which proves that antimony trioxide, samarium trioxide, and zirconium dioxide effectively regulate the phase structure of the ceramic, so that the ceramic is in a pseudo-cubic phase structure in which tetragonal and cubic phases coexist, significantly improving the optical transmittance, piezoelectric properties and mechanical strength of the ceramic material.

[0151] In Comparative Example 4, the titanium dioxide sol is replaced by silica sol, and in Comparative Example 5, the silica sol is replaced by titanium dioxide sol. The composite slurries prepared are sprayed onto the surface of the ceramic substrate. The piezoelectric properties and transmittance of the prepared high-transmittance ceramic materials decrease, which proves that the silica sol and titanium dioxide sol that penetrate into the ceramic matrix can form a silicate glass phase with the ceramic matrix to fill the grain boundary pores, thereby improving the transmittance of the ceramic material, and improving the density and mechanical properties.

[0152] In Comparative Example 6, the composite slurry was replaced with silver slurry sprayed onto the surface of the ceramic substrate. The piezoelectric properties and transmittance of the prepared high-transmittance ceramic material decreased, proving that the silica-titania sol and silver slurry formed a gradient refractive index layer consisting of a silica-titania sol layer and a silver layer on the surface of the ceramic substrate, reducing interface reflection and scattering losses, improving transmittance, and preventing the silver layer from falling off, resulting in a decrease in the transmittance and piezoelectric properties of the translucent ceramic.

[0153] Throughout the specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0154] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a high-transmittance ceramic material, characterized in that: The method comprises the following preparation steps: S1. Take sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide, zirconium dioxide powder raw materials, the powder raw materials were once ball milled and dried to obtain a mixed powder; S2. The mixed powder is pre-sintered, ball-milled twice, and then pressed to form a tablet, which is sintered and polished to obtain a ceramic matrix; S3. Spray the composite slurry onto the surface of the ceramic substrate, heat treat it, and cool it to room temperature to obtain a highly transparent ceramic material.

2. The method for preparing a high-transmittance ceramic material according to claim 1, characterized in that: In step S1, the mass ratio of sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, samarium trioxide, and zirconium dioxide is (2.5-2.6):(3.2-3.4):(13.2-13.5):(0.6-0.8):(0.2-0.3):(0.1-0.2).

3. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S1, the drying temperature is 80-100° C., and the drying time is 20-24 hours.

4. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S1 and step S2, the ball milling is wet ball milling, the ball milling is carried out in a nylon jar, the ball milling medium is ethanol, zirconium balls with a diameter of 8-10 mm are used as grinding balls, the ball-to-material ratio is (1.4-1.6):1, and the ball milling speed is 220-230 r / min; The first ball milling time is 20-24 hours; the second ball milling time is 10-12 hours.

5. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S2, the pre-firing temperature is 800-900°C, the pre-firing time is 4-6 hours, the pre-firing medium is nitrogen, and the nitrogen flow rate is 5-10 L / min.

6. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S2, the pressing pressure is 150-250 MPa; In step S2, the sintering temperature is 1150-1200° C., and the sintering time is 5-7 hours.

7. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S3, the composite slurry is prepared by mixing the silica-titania sol and the silver paste in a mass ratio of 1:(5-10).

8. The method for preparing a highly transparent ceramic material according to claim 7, characterized in that: The silica-titania sol is prepared by mixing silica sol and titania sol in a mass ratio of 1:(0.8-1.2).

9. The method for preparing a highly transparent ceramic material according to claim 1, wherein: In step S3, the heat treatment temperature is 800-900° C., and the heat treatment time is 25-35 minutes.

10. A high-light-transmittance ceramic material prepared by the method for preparing a high-light-transmittance ceramic material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Colored spinel optoceramics

    CN102180662A

  • Method for carrying out surface modification on ceramic material through liquid permeation

    CN103539485A

  • Preparation method of potassium sodium niobate-based piezoelectric ceramic

    CN105541327A

  • Preparation method of xSm-(K0.5Na0.5)NbO3 transparent ceramic

    CN109384465A

  • Antimony-doped potassium-sodium niobate-based transparent ceramic and preparation method thereof

    CN110078506A

Cited By

  • High-performance wear-resistant ceramic material and preparation method thereof

    CN120794582A

  • High-performance wear-resistant ceramic material and method for producing same

    CN120794582B